2022
DOI: 10.3390/su14127508
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Spatial Structure and Regional Interaction of Agricultural Green Total Factor Productivity in China Based on SNA and VAR Methods

Abstract: As regional interaction increases in an open economy, a region’s green total factor productivity in agriculture must be considered alongside relationships with other regions. In this study, the slack-based model (SBM) global Malmquist–Luenberger (GML) index is used to measure the green total factor productivity of agriculture in each province of China, and the social network analysis (SNA) and vector autoregressive model (VAR) impulse response function (IRF) are used to examine the spatial network structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…When the Decision-Making Unit (DMU) was panel data, the Malmquist index could replicate the change in productivity better [ 11 ]. In the case of undesirable outputs, the Malmquist–Luenberger (ML) index, combining the Malmquist index and the Slacks-Based Measure (SBM), was more adaptable [ 18 , 27 ]. However, the ML index did not have the condition of circularity, and there was the possibility of no solution by linear programming.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Decision-Making Unit (DMU) was panel data, the Malmquist index could replicate the change in productivity better [ 11 ]. In the case of undesirable outputs, the Malmquist–Luenberger (ML) index, combining the Malmquist index and the Slacks-Based Measure (SBM), was more adaptable [ 18 , 27 ]. However, the ML index did not have the condition of circularity, and there was the possibility of no solution by linear programming.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, it could be discovered that the research on AGTFP had accomplished fruitful research results, providing strong support for practical research, but there were still two deficiencies in its research. First, there were more studies on the evolution of the time dimension of AGTFP, but the studies from the spatial dimension still needed to be reinforced [ 7 , 18 ]. Second, the interpretation of the convergence mechanism of AGTFP was generally examined from a static perspective, and there was a lack of systematic research on the evaluation of its dynamic angle [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying relationships is the key to analyzing network relationships. The existing research methods for constructing spatial association matrices are mainly the vector autoregressive (VAR) [41] and gravity models [34]. Since VAR models are sensitive to time lags, they are only applicable to data spanning a long period [7].…”
Section: Modified Gravitational Modelmentioning
confidence: 99%
“…Li et al (2019) [54] found that the inter-provincial net agricultural carbon absorption efficiency in China showed a significant positive spatial correlation and there was local clustering; the local spatial autocorrelation Moran's I index also indicated that the inter-provincial net agricultural carbon absorption efficiency showed a clustering effect in space, the above conclusions were consistent with the findings of this paper. Chen et al (2022) [55] also argued that cross-regional cooperation's was critical for green agricultural development. On the other hand, the SDM model showed that Agricultural Industrial Restructuring (AIR), economic development level (RGDP), agricultural infrastructure level (AID), and Environmental Regulation Policies (ERP) had a significant positive effect on local agricultural carbon absorption.…”
Section: Volume 10 -Issuementioning
confidence: 99%